2020
DOI: 10.3389/fpls.2020.00672
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Dynamic Global Transcriptional Atlas Reveals Common Regulatory Networks of Hormones and Photosynthesis Across Nicotiana Varieties in Response to Long-Term Drought

Abstract: Land plants evolve drought acclimation. Existing knowledge of gene regulation mainly comes from short-term drought treatment. However, common regulatory mechanism shared by multiple varieties under long-term drought is little explored. Here we investigated changes in physiology, hormones and transcriptomes in leaves of Nicotiana varieties K326 and Basma Xanthi with/without drought treatment at time courses spanning 1 month. Analyses of deep RNA-Seq data and further full-length Iso-Seq data revealed an atlas of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…Since plant hormone signaling could crosstalk [ 2 ], we checked the change of five hormones in response to BR priming. Without BR priming, a significant increase ( p < 0.05) was observed under drought compared with under well-watered condition for defense associated hormones abscisic acid (ABA), salicylic acid (SA), and 1-aminocyclopropane-1-carboxylic acid (ACC) which is the direct precursor for ethylene ( Figure 4 ), while a significant decrease was found in growth-promoting hormones indole-3-acetic acid (IAA) and gibberellin (GA) under drought compared to those with well-watered condition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since plant hormone signaling could crosstalk [ 2 ], we checked the change of five hormones in response to BR priming. Without BR priming, a significant increase ( p < 0.05) was observed under drought compared with under well-watered condition for defense associated hormones abscisic acid (ABA), salicylic acid (SA), and 1-aminocyclopropane-1-carboxylic acid (ACC) which is the direct precursor for ethylene ( Figure 4 ), while a significant decrease was found in growth-promoting hormones indole-3-acetic acid (IAA) and gibberellin (GA) under drought compared to those with well-watered condition.…”
Section: Resultsmentioning
confidence: 99%
“…Drought or water deficit in soil adversely affects terrestrial crop productivity, thus threatening our food security. Most studies have focused on short-term drought responses, but few studies investigated long-term drought effects which cause agricultural loss [ 1 , 2 , 3 ]. Seasonal drought, mostly belonging to the long-term drought, is the most prevalent environmental factor affecting yield [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the cytokinine signal pathway, DEGs encoding histidine-containing phosphotransferase (AHP) and two-component response regulator ARR-A family (A-ARR4) were upregulated by shade treatments, which is known to interact with shade signal receptor phytochrome B, but the expression of ARR5 was down-regulated, which may be a feedback regulation on more stable ARR5 upon increased cytokinine [46] under shade. In the abscisic acid signal pathway, five DEGs encoding the same abscisic acid receptor PYL family (PYL) were upregulated, which suppressed downstream DEGs encoding protein phosphatase 2C type A (PP2C) and most of the other PP2C types as expected [47] (Figure 9).…”
Section: Regulation Of Degs In Hormone Signalingmentioning
confidence: 64%
“…Our analysis of gene regulation in multiple plant hormone signal pathways revealed that the growth promoting hormones auxin, gibberellin, brassinosteroid, cytokinine and senescing hormones of abscisic acid and ethylene were all stimulated under shade treatment. This could be a crosstalk from a manner of hormone cascaded signaling network [44,47,50]. The regulation on the hormone DEGs activates downstream regulation to promote growth elongation under shade [45].…”
Section: Discussionmentioning
confidence: 99%